Impact of Visual Learning Devices on Secondary School Biology Students’ Academic Performance in Ilorin, Nigeria - Mulkah Adebisi Ahmed; Michael Olubunmi Odewumi (Indonesian Journal of Science and Education (IJOSE), 2020)
Visual learning devices can be instructional tools utilised by the instructors globally. However, despite its relevance for teaching, the awareness of its use have not been notably established. Therefore, the study examined the impact of visual learning devices on secondary school (SS) biology students’ academic performance in Ilorin, Nigeria.  Study was of descriptive of the survey type and sampled were 100 teachers and 139 students in Ilorin, Nigeria. The instrument was the researchers-designed questionnaire which was validated by two Biology educators, two educational technologists and a test, measurement and evaluation specialist. Whereas, the face and content and pilot tested were observed with Cronbach alpha, and reliability coefficients were recorded at 0.05 level of significance. Seven research questions were raised and answered while three research hypotheses were formulated and tested. Findings revealed a significant difference between male and female students; between the students in SS I. II, and III and between the rural and urban schools students on impact of visual learning devices on students’ academic performance. Therefore, the study concluded that visual learning devices has impact on students’ academic performance. Hence, the use of visual learning devices was recommended for all secondary schools in Nigeria for the teaching of Biology. Keyword: learning devices, academic performance, biology students, impact